2007
DOI: 10.1002/ijc.23211
|View full text |Cite
|
Sign up to set email alerts
|

RBP2‐H1/JARID1B is a transcriptional regulator with a tumor suppressive potential in melanoma cells

Abstract: The RBP2-H1/JARID1B nuclear protein belongs to the ARID family of DNA-binding proteins and is a potential tumor suppressor that is lost during melanoma development. As we have recently shown, one physiological function of RBP2-H1/JARID1B is to exert cell cycle control via maintenance of active retinoblastoma protein. We now add new evidence that RBP2-H1/JARID1B can also directly regulate gene transcription in a reporter assay system, either alone or as part of a multimolecular complex together with the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 64 publications
3
56
0
Order By: Relevance
“…However, it has also been suggested that JARID1B itself has a tumor suppressive activity, partly, due to its binding and ability to stabilize hypophosphorylated pRb, leading to maintenance of pRb-mediated cell-cycle control (5). In agreement with this, it has been observed that the expression of JARID1B is lost in the majority of advanced and metastatic melanomas and in many melanoma cell lines (4,7). In this article, we showed that JARID1B is able to suppress angiogenesis and metastasis, supporting the notion that JARID1B itself is a potential tumor suppressor.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, it has also been suggested that JARID1B itself has a tumor suppressive activity, partly, due to its binding and ability to stabilize hypophosphorylated pRb, leading to maintenance of pRb-mediated cell-cycle control (5). In agreement with this, it has been observed that the expression of JARID1B is lost in the majority of advanced and metastatic melanomas and in many melanoma cell lines (4,7). In this article, we showed that JARID1B is able to suppress angiogenesis and metastasis, supporting the notion that JARID1B itself is a potential tumor suppressor.…”
Section: Discussionsupporting
confidence: 67%
“…Subsequently, JARID1B dysregulation has been reported in several types of solid tumors, including prostate cancer (3), melanoma (4-7), and bladder cancer (8). Surprisingly, however, mechanistic studies on the role of JARID1B in different types of cancer have yielded inconsistent and even confusing results (1,3,5,(7)(8)(9)(10). Therefore, the mechanistic role of JARID1B in tumor progression remains an intriguing topic.…”
Section: Introductionmentioning
confidence: 99%
“…pRb phosphorylation leads to cell release from G1 arrest and to promotion entry into the S-phase (36). In addition, JARID1B/ KDM5B, a member of the ARID family, exerts cell cycle control via maintenance of pRb (39). These data allow us to speculate that proteins of the ARID family directly or indirectly regulate the cell cycle, particularly alterations in the cell cycle checkpoint machinery.…”
Section: Identification Of Arid-containing Proteins and Arid1a-interamentioning
confidence: 85%
“…In this study, we demonstrated that JARID1B/KDM5B expression was statistically significantly different between T1 and T3 (c 2 = 5.365, P < 0.05) and grade I and grade II (c 2 = 6.097, P < 0.05) tumors; that JARID1B/KDM5B protein expression in lymph node metastasis groups (N1, N2, N3) was significantly higher than in those tumors without lymph node involvement (N0) (c 2 = 4.295, c 2 = 5.814, and c 2 = 4.812, respectively; P < 0.05). Surprisingly, however, mechanistic studies on the role of JARID1B/KDM5B in different types of cancer have yielded inconsistent and even confusing results (Roesch et al, 2008(Roesch et al, , 2010. In melanocytic tumors, JARID1B/KDM5B was found to be highly expressed in benign nevi, which typically are characterized by oncogene-induced senescence.…”
Section: Discussionmentioning
confidence: 99%